2007
DOI: 10.1111/j.1742-1241.2007.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

A nurse-managed diabetes care programme

Abstract: NMDC programme improves diabetes outcomes more significantly than endocrinologist-directed care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Recent studies have demonstrated that in public health and university centres, nurses that follow treatment algorithms can produce significantly better Data were n (%) or mean ± SD. diabetes outcomes than those can be achieved with physician-directed care (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), even if the physicians are endocrinologists themselves (32). But unfortunately, diabetes care programmes run by health workers without the physical presence of a physician might not be psychologically acceptable to the diabetic patients who choose to seek care in private diabetes or endocrinology clinics or offices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that in public health and university centres, nurses that follow treatment algorithms can produce significantly better Data were n (%) or mean ± SD. diabetes outcomes than those can be achieved with physician-directed care (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), even if the physicians are endocrinologists themselves (32). But unfortunately, diabetes care programmes run by health workers without the physical presence of a physician might not be psychologically acceptable to the diabetic patients who choose to seek care in private diabetes or endocrinology clinics or offices.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore redesigned the delivery of diabetes care and applied it to diabetic patients attending a private endocrinology clinic for a period of 12 months. The new model was a nurse-assisted diabetes care (NADC) instead of a nurse-managed care programme (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). In this model, in terms of task distribution among team members, the pretrained nurse functioned in a complementary capacity.…”
Section: What's Newmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The doctors usually have to deal with other more immediate problems of the patients. 17 All health care workers need to be prepared for the different situations depending on their responsibilities and workplace where patients interact with them. In order for the members of staff to carry out their roles effectively, no matter the level of their career, the knowledge and skills standards have to be set for everyone who is in regular contact with patients with diabetes 8 and other major NCDs.…”
Section: Levels Of Education and Training Of Health Care Workers In Dmentioning
confidence: 99%
“…In their study, Dr Pishad et al. (4) recognise the impact of patient education and intensive management of the individual with diabetes. They note that time constraints and economic realities frequently interfere with their ability to provide that level of care.…”
mentioning
confidence: 99%